PENGARUH PENERIMAAN PAJAK DAN KEPATUHAN KEWAJIBAN PAJAK RUMAH BURUNG WALET TERHADAP PEROLEHAN PAD - Nasution Nasution; Haliah Haliah; Nirwana Nirwana; Ismail Keri (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to find out how the effect of collecting walét bird nest taxes on local revenue for the Luwu Regency government. This study focuses on swallow nest entrepreneurs in Luwu Regency. The technique of collecting data in this research is by using a questionnaire with 9 samples of walét bird entrepreneurs, using multiple linear analysis method. Based on the results of the study, swallow nest collection (X1) and taxpayer compliance (X2) simultaneously have a significant effect on local revenue (Y) in Luwu Regency.